TGR5 receptors in SF1-expressing neurons of the ventromedial hypothalamus regulate glucose homeostasis - Philippe Zizzari; Ashley Castellanos-Jankiewicz; Selma Yagoub; Vincent Simon; Samantha Clark; Marlene Maître; Nathalie Dupuy; Thierry Leste-Lasserre; Delphine Gonzales; Kristina Schoonjans; Valérie S. Fénelon; Daniela Cota (Molecular Metabolism)
Objective: Steroidogenic factor-1 (SF1) neurons of the ventromedial hypothalamus play key roles in the regulation of food intake, body weight and glucose metabolism. The bile acid receptor Takeda G protein-coupled receptor 5 (TGR5) is expressed in the hypothalamus, where it determines some of the actions of bile acids on food intake and body weight through still poorly defined neuronal mechanisms. Here, we examined the role of TGR5 in SF1 neurons in the regulation of energy balance and glucose metabolism. Methods: We used a genetic approach combined with metabolic phenotyping and molecular analyses to establish the effect of TGR5 deletion in SF1 neurons on meal pattern, body weight, body composition, energy expenditure and use of energy substrates as well as on possible changes in glucose handling and insulin sensitivity. Results: Our findings reveal that TGR5 in SF1 neurons does not play a major role in the regulation of food intake or body weight under standard chow, but it is involved in the adaptive feeding response to the acute exposure to cold or to a hypercaloric, high-fat diet, without changes in energy expenditure. Notably, TGR5 in SF1 neurons hinder glucose metabolism, since deletion of the receptor improves whole-body glucose uptake through heightened insulin signaling in the hypothalamus and in the brown adipose tissue. Conclusions: TGR5 in SF1 neurons favours satiety by differently modifying the meal pattern in response to specific metabolic cues. These studies also reveal a novel key function for TGR5 in SF1 neurons in the regulation of whole-body insulin sensitivity, providing new insight into the role played by neuronal TGR5 in the regulation of metabolism.